LEGAL PROTECTION FOR E-BOOK CREATORS ON GRAMEDIA DIGITAL APPLICATION - Moh. Rafiqi Luthfi Rahman; Hardian Iskandar; Dodi Jaya Wardana (Universitas Muhammadiyah Gresik, 2022)
copying more widespread. One of the studies examined by the author is the E-Book in the Gramedia Digital application. The purpose of this study is to explain how the legal protection of the creator and the legal consequences for the perpetrators as well as the settlement of disputes against the duplication of the ebook creator's work on the digital gramedia application. The research method used is a normative legal research method, with a statutory approach (Statue Approach) and a conceptual approach (Conceptual Approach). The results obtained from this study found Gramedia Digital provides legal protection in the form of technology that can record and mark traces of user activities which will later be stored as digital track records with the aim of legal protection for the creator of the E-Book itself. The legal consequences of duplicating E-Books on the Gramedia Digital application are subject to soft blocks in the form of suspension and account closure. Gramedia digital explained that they cooperate with any legal process (local law, provincial law and national law). Then the settlement of E-Book disputes is also explained through litigation (court) and non-litigation (outside court